(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Household expenditure survey of Erbil governorate in 2007 have been used to estimate Engel’s curves using OLS method for (12) and (11) of general and foodstuff items, respectively. Two dummy variables have been used as explanatory variables, one representing the geographic regions, and the other represents four expenditure groups. The study aimed to estimate the expenditure elasticity of various Expenditure items, as well as predict the demand for food. The results indicated that two main explanatory variables, namely; gross and food expenditure, have significant effect on the changes that took place for expenditures of the items under consideration, as well as results showed that estimated expenditure elasticities are consistent with the theoretical criteria. . The most important conclusions reached are: response of food items to total food expenditure is greater than their response to gross expenditure, values of expenditure elasticity for (82%) of food items are less than (1), which indicate that they are necessary and have not been satisfied, existence of significant differences of living between rural and urban areas on the one hand, and between the lower and upper expenditure groups, on the other hand, according to the food proportion expenditure and its elasticity . Lastly, variation of expenditure elasticity from one group to another, and from region to region, complicates process of forecasting and planning for consumption.